Design of flight control system and autopilots for solar UAV : part 1 - Ang, Swee Huat (2014)
This report encompasses the preliminary design stages of the software for the Flight Control System of the Solar-Powered Unmanned Aerial Vehicle (Solar UAV) project that is carried out in Nanyang Technological University (NTU) in collaboration with IIT Kanpur and supported by DSO National Laboratories. The conceptual review for six degrees-of-freedom modelling as well as the modern control theory is done before applying them to the design of the offline simulation model. The overall simulation model is done on the MATLAB-SIMULINK platform that includes the control blocks which formed the main portion of the design verification process. These control blocks are supported by other simulation blocks such as disturbance blocks and time histories, that are part of the MATLAB-SIMULINK software and do not take part in the verification processes. Instead, the entire offline model was run with arbitrary values, taken out from “Flight Stability and Automatic Controls by Robert C. Nelson” which concluded the entire verification process. In addition to the software code development, a design strategy for obtaining the optimal feedback gains for the controls is also elaborated where iterations upon an initial guess is to be carried out. This project is but a small portion of the entire Flight Controls System for the Solar UAV and future works, such as procurement of hardware and hardware-software integration are recommended to complement the work presented in this report so as to achieve the main objective which is autonomous flying of the Solar UAV.